The role of psychological factors in aetiopathogenesis and management of obesity related diseases - Tripathi J.S., Byadgi P.S., Narasimha Murthy K. (Journal of Applied Pharmaceutical Science)
The obesity is a challenging problem in to-days world which if left un tackled leads to a variety of associated illnesses like Hypertension, Diabetes mellitus, Cardiovascular disorders, Cerebro vascular accidents etc. The common etiological factors which are implicated include sedentary life style, genetic factors, dietary factors and endocrine factors, but the psychological factors are often overlooked which are the most important factor perpetuating binge eating behavour. The emotional instability, depression, stress, sexual abuse etc, often result in compulsive over eating leading to obesity. Thus the comprehensive management of obesity and the associated illnesses should include the proper tackling of these psychological components apart from other common therapies. The present article critically analyses the role of these factors in the causation of obesity and its different management strategies which includes sattvavajaya as an Ayurvedic technique.
Keywords: Obesity, Depression, Hypertension, Psychosomatic, Sattvavajaya, Behavior modification.